Bases for the digital transformation of the productive sector: an exploratory study of key competencies in Peru - Regalado-Pezúa, Otto (2021)
The main objective of this research is to determine the basis of the key competencies necessary to achieve the digital transformation of public and private organizations in Peru. With this objective in mind, the conceptual framework involves the definition of a digital transformation in organizations and their impact on those organizations. Secondly, the article presented the results of the exploratory fieldwork conducted through in-depth interviews with ten executives from different productive sectors and analyzed them through content analysis. From this exploratory study, it concludes that all the experts interviewed agree on: i) the urgency of initiating a digital transformation process in small, medium, and large companies; ii) the need for training in digital transformation for company employees in all functional lines, giving priority to the commercial area; and iii) investment in the implementation process starting with cybersecurity and big data due to the impact on the operational and commercial results of the companies.